SELLING PHILANTHROPY: A CRITICAL DISCOURSE ANALYSIS OF ‘RARE IMPACT FUND WITH SEPHORA’ INSTAGRAM CAMPAIGN - Cahyaratu Ayuningtyas; Suhandoko (2025)
Famous brands often incorporate charitable initiatives into their business strategies. While such practice is often perceived as genuine corporate social responsibility, it may also function as marketing tools to enhance the brand prestige and even profitability. This study examined how Rare Beauty, a renowned cosmetic brand owned by Selena Gomez, an American actress, utilizes social media campaigns to encourage consumer purchase under the guise of supporting mental health awareness. By analysing three campaign videos featuring Selena Gomez, released in October 4 and 10, 2023, this study employed Normal Fairclough’s three-dimensional Critical Discourse Analysis model to reveal how campaign narratives cloaks capitalist motives in humanitarianism rhetoric. Additionally, public perception was also evaluated through an examination of 21 most-liked comments on the campaign posts. The study demonstrates how the brand capitalizes on public altruism to increase its corporate image. At the textual level, Selena Gomez consistently initiates her campaign by addressing mental heal issues, followed by explicit calls to purchase products. Her use of inclusive “we,” bold claims such as “100% of the profits donated,” and emotive words (e.g., “together,” “incredible,” and “yummy”) serve to obscure the hidden commercial agenda. On the discourse level, Instagram’s features, such as the inclusion of celebrity (happens to be the company owner) voice-overs, swipeable slides, and call-to-action links, were strategically used to construct the purchasing act as a morally and even commendable form of charity. At the social practice level, the study found that the packaging of capitalism within humanitarianism is driven by the tendency to target women through emotional appeals, particularly by utilizing social issues tied to women empowerment. Thus, link cosmetic purchase to social causes seems to be an effective marketing strategy. Unfortunately, an analysis of netizen reactions reveals polarized responses; while many criticize Selena Gomez for being hypocrite, by advocating for mental health while remaining silent on the physical and mental health of war victims in Gaza, few demonstrate awareness of the capitalist mechanisms masked by humanitarianism discourse.